2010
DOI: 10.1007/s00436-010-1932-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toll-like receptor 2 (TLR2) polymorphisms and asymptomatic bancroftian filariasis

Abstract: Lymphatic filariasis is mainly caused by the filarial nematodes Wuchereria bancrofti and Brugia malayi. Wolbachia, intracellular symbiotic bacteria in filarial parasite, is known to induce immune response predominantly through Toll-like receptor 2 (TLR2). This study was performed to investigate the association between polymorphisms of the TLR2 gene and susceptibility to asymptomatic bancroftian filariasis. A total of 142 unrelated asymptomatic bancroftian filariasis patients and 151 endemic normal controls in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
(52 reference statements)
0
37
0
1
Order By: Relevance
“…Moreover, associations between the TLR2 genetic diversity and Alzheimer's disease [61] or cognitive function in schizophrenia [62] are highly suggestive of genetically-driven inter-individual ability to modulate neuroinflammatory processes. Of importance is that the TLR2 rs3804099 polymorphism was showed on the one hand to be associated with several inflammatory and infectious diseases including pulmonary tuberculosis, neonatal infection, filariasis, ocular Behcet's disease and cancer [63][64][65][66][67] and to exert a functional impact on the inflammatory response on the other [65,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, associations between the TLR2 genetic diversity and Alzheimer's disease [61] or cognitive function in schizophrenia [62] are highly suggestive of genetically-driven inter-individual ability to modulate neuroinflammatory processes. Of importance is that the TLR2 rs3804099 polymorphism was showed on the one hand to be associated with several inflammatory and infectious diseases including pulmonary tuberculosis, neonatal infection, filariasis, ocular Behcet's disease and cancer [63][64][65][66][67] and to exert a functional impact on the inflammatory response on the other [65,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Once PAMPs are recognized by leucine-rich domains, the signal cascades are initiated, and remarkable proinflammatory cytokines and chemokines, as well as costimulatory molecules, are ultimately induced through the activation of a variety of transcriptional complexes including NF-ÎșB and AP-1 [11][12][13][14][15]. Additionally, host susceptibility to infectious diseases may be associated with the TLRs' polymorphisms [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, some infections have been associated with TLR polymorphisms. The TLR2 haplotype 196-174 del was found to be strongly associated with an increased risk of asymptomatic bancroftian filariasis [9]. In a study on neurocysticircosis (NCC), TLR4 Asp299Gly and Thr399Ile polymorphisms were associated with its occurrence (P < 0.001 for Asp299Gly; P = 0.003 for Thr399Ile) and progression to symptomatic NCC, compared with control subjects or asymptomatic NCC [20].…”
Section: Discussionmentioning
confidence: 99%
“…Various TLR polymorphisms have been implicated in susceptibility and progression of diseases like neurocysticercosis, Hepatitis C virus, asthma, cervical cancer and asymptomatic filariasis [9]- [11]. A few previous studies have reported that intestinal and biliary invasion of Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%